2021
DOI: 10.3390/ijerph182413273
|View full text |Cite
|
Sign up to set email alerts
|

Morphing Task: The Emotion Recognition Process in Children with Attention Deficit Hyperactivity Disorder and Autism Spectrum Disorder

Abstract: Recognizing a person’s identity is a fundamental social ability; facial expressions, in particular, are extremely important in social cognition. Individuals affected by autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD) display impairment in the recognition of emotions and, consequently, in recognizing expressions related to emotions, and even their identity. The aim of our study was to compare the performance of participants with ADHD, ASD, and typical development (TD) with reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 68 publications
0
14
0
1
Order By: Relevance
“…In contrast, Buongiorno et al (2020) reported that children with ADHD exhibited more difficulty in surprise recognition (p = .00). This was supported by Greco et al (2021), who found that children with ADHD had a higher percentage of error recognition for surprised human faces compared with controls (p = .049) Neutral Expressions Airdrie et al (2018) reported significantly lower accuracy in identifying neutral facial expressions in adolescents with ADHD compared with that in control participants (p < .5). This was consistent with the results of children assessed by Kara et al (2017) (clear face emotions, p = .03; cropped eye emotions p = .026) and Buongiorno et al (2020) (p = .00).…”
Section: Sadnessmentioning
confidence: 72%
See 2 more Smart Citations
“…In contrast, Buongiorno et al (2020) reported that children with ADHD exhibited more difficulty in surprise recognition (p = .00). This was supported by Greco et al (2021), who found that children with ADHD had a higher percentage of error recognition for surprised human faces compared with controls (p = .049) Neutral Expressions Airdrie et al (2018) reported significantly lower accuracy in identifying neutral facial expressions in adolescents with ADHD compared with that in control participants (p < .5). This was consistent with the results of children assessed by Kara et al (2017) (clear face emotions, p = .03; cropped eye emotions p = .026) and Buongiorno et al (2020) (p = .00).…”
Section: Sadnessmentioning
confidence: 72%
“…Waddington et al (2018) described similar FER performance in children with ADHD, those with ASD, and a comorbid ASD + ADHD group. Deficits in FER may be an overlapping feature of children with ADHD and ASD, as suggested by Greco et al (2021). Airdrie et al (2018) simultaneously assessed eye movements during a FER task and found that adolescents with ADHD and conduct disorder symptoms spent less time focusing on the eye region of the face than controls.…”
Section: Evidence For Abnormal Fer As a Secondary Deficit In Adhd Pat...mentioning
confidence: 95%
See 1 more Smart Citation
“…Other emotional symptoms reported include emotional immaturity, obsessive-compulsive behaviours, impulsivity and behavioural dysregulation. ASD or ASD-like symptoms and ADHD have been described [ 54 , 55 ]. Patients with 48, XXYY also have generalised difficulties with socialization and communication.…”
Section: Discussionmentioning
confidence: 99%
“…Children with ASD, ADHD, and OCD differentiated less between dynamic faces and dynamic flowers, with most of the effects seen in the occipital and temporal regions, suggesting that emotional difficulties shared in NDDs may be partly attributed to shared atypical visual information processing [ 54 ]. Another similar study conducted by using a morphing technique demonstrated a faster response time in neurotypical children compared to ASD and ADHD children, with ADHD participants performing better than ASD participants on the same task [ 55 ]. These studies have shown that there is an impairment of emotion recognition in neurodevelopmental disorders, leading to our decision to work on this skill in our neuro-psychomotor training.…”
Section: Discussionmentioning
confidence: 99%